Forensic Analysis of the Disputes Typology of the NSW Construction Industry Using PLS-SEM and Prospective Trend Analysis - Rahnamayiezekavat, Payam; Sorooshnia, Ehsan; Rashidi, Maria; Faraji, Amir; Mostafa, Sherif; Moon, Sungkon (Buildings, 2022)
Project claim management is the central pillar of the overlapping areas of contract administration, contract law and building regulations. Delays caused by inefficiency of the procedures designed to avoid disputes emerge at the pre-project phase and continue during construction. The quantum of research addressing this issue is not immediately transferrable between jurisdictions, mainly due to local specificity of construction practices, contract and construction laws, as well as clients’ preferences. The primary aim of this study is to identify the underlying causes of disputes that have arisen in the NSW construction industry in the past two decades and to analyze the inter-relationships between the causes. To achieve this purpose, PLS-SEM quantitative models were utilized to study different factors influencing disputes. Through a detailed quantitative analysis of 230 cases, based on dispute frequencies, causes and effect analysis and the resultant loop cause diagrams, the dispute triggers, types, and root causes have been analyzed as the basis for developing a model to predict the future likelihood of disputes. Finally, 13 causes of disputes have been recognized as the main causal factors in the construction projects in NSW. This study also has shown that payment and reimbursement-related disputes are the most frequent in NSW construction, except for the last two years.
Keywords: Causal Analysis; construction; dispute; Forensic Analysis; PLS-SEM; Trend Analysis